SIMBA SEHATI: UPAYA PENYELAMATAN DAN PERBAIKAN LINGKUNGAN MELALUI EDUKASI GENERASI MUDA DI DESA KELUANG, KABUPATEN BANYUASIN, SUMATERA SELATAN - Eka Aprillia; Jalu Tathit Pancapurna Satya (Transpublika Publisher, 2023)
The SIMBA SEHATI program in Keluang Village, initiated by PT Pertamina EP Ramba Field, aims to preserve and improve the environment through education of the younger generation in line with the government's Adiwiyata program. Implemented at SMP Negeri 2 Tungkal Ilir, this program involves 300 students and teachers as beneficiaries and program implementers. Activities carried out include maggot cultivation, school waste bank management, waste water management, organic fertilizer making, and many more. Through this program, it is hoped that the beneficiaries can become school health ambassadors and apply their knowledge to the community in Keluang village.